The Oxford handbook of phenomenological psychopathology - Stanghellini, Giovanni; Raballo, Andrea; Broome, Matthew R.; Fernandez, Anthony Vincent; Fusar-Poli, Paolo; Rosfort, René (Oxford University Press, 2019)
For about one century the catalogue of books in phenomenological psychopathology has been tremendously rich in essays, but remarkably poor in handbooks. Even the cornerstone of our canon, Jaspers' General Psychopathology, originally written as a textbook, can hardly be given to a student as a basic reading. This makes teaching the fundamentals of the discipline difficult. Students ask for manualised knowledge expecting teachers to explain what must be done in a given circumstance. This Handbook is meant to fill these gaps. It includes a detailed, thorough and reader-friendly description of philosophical and clinical key-concepts and constructs, and of the contributions of leading figures of phenomenological psychopathology.
Includes bibliographical references
This handbook is currently in development, with individual articles publishing online in advance of print publication. At this time, we cannot add information about unpublished articles in this handbook, however the table of contents will continue to grow as additional articles pass through the review process and are added to the site
Keywords: Aufsatzsammlung; Psychopathologie